Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13046-020-1530-3
|View full text |Cite
|
Sign up to set email alerts
|

Pin2 telomeric repeat factor 1-interacting telomerase inhibitor 1 (PinX1) inhibits nasopharyngeal cancer cell stemness: implication for cancer progression and therapeutic targeting

Abstract: Background: Recurrence and distant metastasis are still the main factors leading to treatment failure for malignant tumors including nasopharyngeal carcinoma (NPC). Therefore, elucidating the molecular mechanisms underlying nasopharyngeal carcinoma metastasis is of great clinical significance for targeted gene therapy and prognostic evaluation. PinX1, a tumor suppressor gene, was previously demonstrated to be a powerful tool for targeting telomerase in order to resist malignant tumor proliferation and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Furthermore, ~80% lung cancer cases are non-small cell lung cancer (NSCLC), and lung adenocarcinoma is the most common subtype of NSCLC ( 1 ). Tumor metastasis is the main cause of clinical treatment failure and mortality ( 2 ). Lung adenocarcinoma is a type of lung cancer that easily metastasizes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ~80% lung cancer cases are non-small cell lung cancer (NSCLC), and lung adenocarcinoma is the most common subtype of NSCLC ( 1 ). Tumor metastasis is the main cause of clinical treatment failure and mortality ( 2 ). Lung adenocarcinoma is a type of lung cancer that easily metastasizes.…”
Section: Introductionmentioning
confidence: 99%
“… 101 As a tumor suppressor gene, Pin2 telomeric repeat factor 1-interacting telomerase inhibitor 1 (PinX1) inhibits cell proliferation, migration, and invasion by regulating p53/miR-200b-mediated transcriptional inhibition of Snail1, Twist1, and Zeb1, thereby inhibiting EMT of CD133(+) cancer stem cells (CSCs) in NPC. 102 Furthermore, Zhao et al 103 found that cisplatin treatment can induce the upregulation of miR-125a and miR-125b expression, and these miRNAs can target p53 mRNA and reduce p53 protein-induced apoptosis, which may be one of the causes of cisplatin resistance in NPC cells.…”
Section: Crucial Signal Pathways Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…We have previously reported roles for PinX1 in modulating proliferation, apoptosis, EMT, and stemness in NPC cells 19 . Here, we investigated the mechanisms whereby PinX1 in uences proliferation, apoptosis, and autophagy in NPC cells.…”
Section: Discussionmentioning
confidence: 97%